A indisciplina escolar nas pesquisas acadêmicas - Ledo, Valdir Aguiar (2009)
This work aims the study of school indiscipline in the academic research. More precisely, it is based on biographical research carried out by means of survey and analysis of Doctor s degree dissertations and Master s degree theses in PUC-SP (Pontific Catholic University of São Paulo) and FEUSP (College of Education at the University of São Paulo), produced in post-graduation Programs in Education from 2000 to 2006. The institutes and periods were determined due to the production amount at the related theme. Before the research analysis on the subject, a mapping was accomplished related to the national production on both school discipline and indiscipline from 1987 to 2006. It was performed based on the on-line database of CAPES (Coordination for the Improvement of Higher Education Personnel). After the mapping, ten researches about school indiscipline carried out at PUC-SP and USP were analyzed focusing on their methodological issues, objectives, hypotheses and justifications. In those works, the indiscipline acts were identified. Then, the works contents were discussed, focusing on the following aspects: reference to the students and teachers; reference to the family and school; reference to the local context, to the teaching system and to the social context. At last, the researchers proposals and recommendations directed to the schools and teachers with the purpose of softening the disciplinary issues were pointed out